Postprandial Mineral Metabolism and Secondary Hyperparathyroidism in Early CKD - Isakova, Tamara; Gutierrez, Orlando; Shah, Anand; Castaldo, Lorraine; Holmes, Julie; Lee, Hang; Wolf, Myles (Journal of the American Society of Nephrology, 2008)
Normophosphatemia and normocalcemia are maintained in chronic kidney disease (CKD) by increased levels of fibroblast growth factor-23 (FGF-23) and parathyroid hormone (PTH), but the stimuli for secretion of these hormones in early CKD are incompletely understood. Most human physiologic studies have focused on random or fasting measurements of phosphorus, calcium, FGF-23, and PTH, but in this study, the hypothesis was that measurements in the postprandial state may reveal intermittent stimuli that lead to increased FGF-23 and PTH levels. The 4-h postprandial response in 13 patients with CKD and fasting normophosphatemia and normocalcemia (mean GFR 41 +/- 8 ml/min per m(2)) was compared with 21 healthy volunteers. Compared with healthy subjects, fasting patients with CKD had significantly higher levels of FGF-23 and fractional excretion of phosphorus; lower fractional excretion of calcium; and no difference in serum calcium, phosphorus, and PTH levels. After standardized meals, urinary phosphorus excretion in both groups increased despite unchanged serum phosphorus and FGF-23 levels. Postprandial urinary calcium excretion also increased in both groups, and this was accompanied by significantly reduced serum calcium and increased PTH levels in patients with CKD only; therefore, FGF-23 does not seem to be an acute postprandial regulator of phosphaturia in CKD or in health, but inappropriate postprandial calciuria with episodic, relative hypocalcemia may represent a previously unreported mechanism of secondary hyperparathyroidism in CKD.